Decentralisation, local eonomic development and urban agriculture in Zambia. - Hampwaye, Godfrey (My University, 2008)
ABSTRACT This study analyses decentralisation, local economic development (LED) and urban agriculture in Zambia focusing attention on the cities of Lusaka, Ndola and Kitwe. LED is examined in terms of the formulation and implementation of LED plans following the downturn in the local economies of all the three case studies. A key focus is on urban agriculture, especially the institutional responses by the three local governments towards this activity. This study draws from a wide range of primary sources. Focused interviews were conducted with key stakeholders and interview schedules were administered to urban cultivators. Further, government documents were used to achieve certain objectives of the study. The results of the study show that although the three case studies generally indicate an inadequate capacity, especially fiscal capacity, to deliver public services, there are variations from city to city. The results show that Lusaka has the best capacity while Ndola has the least capacity among the three cities. Capacity constraints in these councils have ramifications for the implementation of the decentralisation policy in Zambia. In terms of local economic development initiatives, all the case studies show attempts to formulate local development plans albeit only limited implementation of these plans has taken place as a result of financial constraints. In addition, the results show that urban agriculture is increasingly becoming an important community response by the residents of these cites despite the fact that the local authorities do not provide support services to urban cultivators.